STRATEGY TO IMPROVE EDUCATION QUALITY THROUGH GIVING REWARDS TO STUDENTS AT MIN 6 NGANJUK - Muhammad Yusuf; Khafita Vianti Mala (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2022)
Abstract In the era of globalization, improving the quality of competitive education is very necessary. All problems in education such as not focusing on learning, declining student enthusiasm and so on are challenges for school principals, educators and parents. Therefore, the provision of giving rewards is expected to improve the quality of education. This study focuses on strategies to improve the quality of education through rewards to students along with supporting and inhibiting factors in its implementation. This research uses a qualitative approach with a descriptive type of research. The results of the study show that the strategy for improving the quality of education through the provision of rewards refers to input (preparation of teacher human resources), process (class division, procurement of extracurricular and tutoring, giving rewards that have applied the principles and meet the requirements), output (rewards foster student enthusiasm, and assessment can create output according to the educational goals of the institution) with various supporting factors such as the involvement of several parties, adequate infrastructure, student motivation and sufficient funds. And the obstacles to its implementation are poor time management, urgent interests in school, lack of concern for some students, and lack of full support from parents. Overcome by paying attention to teachers, students and parents who can support the implementation of school activities. And with the implementation of this strategy, the educational process makes it easier for teachers to deliver subject matter, the direct results of education are in the form of student behavior after attending lessons, and the final result of education is the behavior of graduates.